USE OF DIAGNOSTIC SSR MARKERS FOR IDENTIFICATION OF LARIX LYALLII AND L. OCCIDENTALIS (PINACEAE) - NADEEM, S.; JAQUISH, B.; NEWTON, C.; KHASA, P. D. (Edinburgh Journal of Botany, 2003)
Two species-specific microsatellite or simple sequence repeat (SSR) markers (UAKLly10a and UAKLla1) were used to distinguish Larix lyallii Parl. (subalpine larch) from L. occidentalis Nutt. (western larch) (Pinaceae). These markers can easily be used for rapid identification of the two species at any stage in the sporophyte phase of the life cycle. In the future, they should prove to be an invaluable tool for determining the possible occurrence and magnitude of introgressive hybridization in overlap zones between the two species. They are also expected to be useful in validating controlled crosses between L. lyallii and L. occidentalis and for certification purposes in reforestation and tree improvement programmes aimed at producing genetically improved hybrid stock.